A short review of diagnosis and compression theapy of chronic venous insufficiency - Kecelj, Nada (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2008)
Introduction: Chronic venous insufficiency (CVI) is a venous disorder in the lower extremities associated with changes in the skin and subcutaneous tissue.Treatment with short-stretch compression bandages is highly recommendedfor advanced stages of CVI. Methods: The compression systems Rosidal Sys, Porelast, CobanTM, and ProguideTM were evaluated in 4 groups of mobile and active patients (n = 18) with CVI stage II or III. Sub-bandage pressures at point B1 were measured in the upright and supine positions 30 minand 12 h after the bandage was applied. Average pressures and values of thestatic stiffness index (SSI) were calculated for each group. Results: The Porelast, Rosidal Sys and CobanTM systems had SSI values in excess of 10 mmHg,30 min and 12 h after application. The corresponding values for ProguideTM were below 10 mmHg. Conclusion: Porelast, Rosidal Sys and CobanTM are very stiff systems, whereas ProguideTM is more similar to long-stretch compression bandages with a lower degree of stiffness.
Keywords: diagnostika; kronična venska insuficienca; Occlusive Dressings; Okluzivne obveze; therapy; vene; Venous Insufficiency; Venska insuficienca; zdravljenje